Functional Abilities of Children as Factors of School Achievement - Đoković, Sanja T.; Kovačević, Tamara R.; Ostojić Zeljković, Sanja B. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Understanding the factors which affect students’ school achievement is an important knowledge source for strategic planning and encouraging changes in education. In this paper, we focused on examining the factors related to personal characteristics. The aim of this research was to determine the relation between school failure and achievements in certain functional abilities, such as: academic skills (reading, writing), attention, communication (receptive and expressive speech), class participation, and behavior. The sample included 195 younger school-age children of both genders. Students’ functional abilities were assessed by the S.I.F.T.E.R. scale (Screening Instrument for Targeting Educational Risk). The results showed that school achievement correlated with all assessed functional abilities. The coefficient of multiple determination showed that 48% of individual differences in children’s school achievement can be explained by individual differences in the given model of functional abilities. It should also be emphasized that only two functional abilities, attention and communication, were singled out as statistically significant particular predictors.